2010
DOI: 10.1007/s00702-010-0383-x
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of CβS 844ins68 and MTHFD1 G1958A polymorphisms with Alzheimer’s disease in Chinese

Abstract: Folate deficiency and elevated plasma homocysteine play important roles in pathogenesis of Alzheimer's disease (AD). The aim of this study was to test the association of folate metabolism-related genes, cystathionine beta-synthase gene (CbetaS) and 5, 10-methylenetetrahydrofolate dehydrogenase gene (MTHFD1), with sporadic AD. The CbetaS 844ins68 polymorphism was determined by PCR and the MTHFD1 G1958A single nucleotide polymorphism (rs2236225) by PCR-RFLP. No significant difference of allele and genotype contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Polymorphisms in cystathionine beta synthase (CBS), catalyzing the conversion of homocysteine to cystathionine, are well-known risk factors for AD (Perluigi and Butterfield 2012). These gene polymorphisms are known to decrease CBS activity and cause a high concentration of homocysteine and a low concentration of cystathionine (Bi et al 2010), in line with our observations in C. elegans .…”
Section: Resultssupporting
confidence: 92%
“…Polymorphisms in cystathionine beta synthase (CBS), catalyzing the conversion of homocysteine to cystathionine, are well-known risk factors for AD (Perluigi and Butterfield 2012). These gene polymorphisms are known to decrease CBS activity and cause a high concentration of homocysteine and a low concentration of cystathionine (Bi et al 2010), in line with our observations in C. elegans .…”
Section: Resultssupporting
confidence: 92%
“…The presence of MTHFD1 rs2236225 polymorphism has been described as maternal and offspring risk factor for several conditions, including neural tube defects (Etheredge et al, ), severe placental abruption and miscarriage (Parle‐McDermott et al, , b), intrauterine growth restriction (Furness et al, ), and congenital heart defects in children (Christensen et al, ). Furthermore, rs2236225 was associated with decreased risk for lung cancer (Liu et al, ), but not in cancers of prostate (Collin et al, ), cervix (Mostowska et al, ), and ovaries (Pawlik et al, ), and the A variant allele was also suggested as a risk factor for early onset Alzheimer's disease (Bi et al, ). There are few studies describing the association of rs2236225 polymorphism and maternal risk for NSCL/P, and the results are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Condensation of this amine intermediate 15 with succinic or pimelic acid anhydride in 1,4-dioxane and subsequent esterification afforded ester compounds, and then the ester groups were treated with NH 2 OH•HCl in methanol to obtain compounds 10a-b. 42 Compounds 11a-b were prepared by following the methods described in Scheme 2. The starting material 17 was synthesized in a similar manner of step 1 of Scheme 1, then the ester group was hydrolyzed under basic conditions to yield acid analogue 18, which was coupled with amino acid esters (n = 3 or 5) and the target compounds were achieved by transforming the ester to the hydroxamate group.…”
Section: Chemistrymentioning
confidence: 99%